(3GdCQHYhf MOjKG aj LhGeY Gdcde GdbOSjIs - (3GdgQhj, GdbGQj, CHh GdMSf, fhQ GdOjf (B- (3GdeqdG, Ydj Hf (B((3SdWGf(B) (3eMeO, (B1014 (3g`s ((3YKeGf Hf hdjs)
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg GdYdj GdYXje hHYO abO SfM aj NGWQ Ydj Hf SdWGf Hf eMeO GdbGQj Cf jLeY ef GdCMGOjK GdbOSjI CQHYjf MOjKG HQhGjI UOQ GdQhGIs
(3BNQgG (B:s
(3GdCQHYhf (B: (3Yf CHj gQjQI QVj Gddg Yfg bGd bGd QShd Gddg Udi Gddg Ydjg hSde (B:" (3Ef Gddg JYGdi jbhd jhe GdbjGeI Cjf GdeJMGHhf dLdGdj Gdjhe CXdge aj Xdj jhe dG Xd EdG Xdj (B" (3QhGg CMeO heSdes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B5 / 12s
(3eYLe GdeDdajf (B2 / 446s
(3cTa GdXfhf (B1/ 61s
(3gOjI GdYGQajf (B1 / 751s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMOjK hGdeUWdMs